Pendugaan Volume, Biomassa dan Cadangan Karbon di Atas Permukaan Tanah Pada Kawasan Hutan Desa Lampo Kecamatan Banawa Tengah Kabupaten Donggala - Andriani, Odilia Angly; Hamzari, Hamzari; Misrah, Misrah; Hamka, Hamka (Jurnal Warta Rimba, 2021)
Biomass is the mass of the living vegetation, which also plays an important role in the carbon cycle. Meanwhile, carbon stock is the carbon content stored either on the soil surface as plant biomass, necromass, or in the soil as soil organic matter. Before counting the biomass and carbon stock, we have to count the volume in the tree first. The purpose of this research was to estimate the volume, biomass and aboveground carbon stock stored in the Village Forest area in Lampo Village. This research was conducted for three months, from July 2020 - September 2020 in the Forest Area in Lampo Village, Banawa Tengah District, Donggala Regency. The results of this research showed that the total volume of vegetation in the Lampo Village Forest was 140.17 mÂ³ / ha (trees) and 9.86 mÂ³ / ha (poles); vegetation biomass in Lampo Village Forest is 137.09 tonnes / ha (trees) and 10.00 tonnes / ha (poles); and carbon reserves in Lampo Village Forest are 68.55 tonnes / ha (trees) and 5.00 tonnes / ha (poles). The dominant species group is Bayur (Pterospermum javanicum), of the 8 identified stands.Keywords: Allometrics, Biomass, Carbon Stock